A Novel and Highly Regioselective Synthesis of New Carbamoylcarboxylic Acids from Dianhydrides - Adrián Ochoa-Terán; Jesús Estrada-Manjarrez; Marisela Martínez-Quiroz; Marco A. Landey-Álvarez; Eleazar Alcántar Zavala; Georgina Pina-Luis; Hisila Santacruz Ortega; Luis Enrique Gómez-Pineda; José-Zeferino Ramírez; Daniel Chávez; Julio Montes Ávila; Victoria Labastida-Galván; et al. (The Scientific World Journal)
A regioselective synthesis has been developed for the preparation of a series of N,N′-disubstituted 4,4′-carbonylbis(carbamoylbenzoic) acids and N,N′-disubstituted bis(carbamoyl) terephthalic acids by treatment of 3,3′,4,4′-benzophenonetetracarboxylic dianhydride (1) and 1,2,4,5-benzenetetracarboxylic dianhydride (2) with arylalkyl primary amines (A-N). The carbamoylcarboxylic acid derivatives were synthesized with good yield and high purity. The specific reaction conditions were established to obtain carbamoyl and carboxylic acid functionalities over the thermodynamically most favored imide group. Products derived from both anhydrides 1 and 2 were isolated as pure regioisomeric compounds under innovative experimental conditions. The chemo- and regioselectivity of products derived from dianhydrides were determined by NMR spectroscopy and confirmed by density functional theory (DFT). All products were characterized by NMR, FTIR, and MS.